Troy, a tumor necrosis factor receptor family member, interacts with lgr5 to inhibit wnt signaling in intestinal stem cells - Fafilek, Bohumil; Krausova, Michaela; Vojtechova, Martina; Pospichalova, Vendula; Tumova, Lucie; Sloncova, Eva; Huranova, Martina; Stancikova, Jitka; Hlavata, Adela; Svec, Jiri; Sedlacek, Radislav; Luksan, Ondrej; et al. (Gastroenterology, 2013)
BACKGROUND & AIMS: The Wnt signaling pathway is required for maintenance of the intestinal epithelia; blocking this pathway reduces the proliferative capacity of the intestinal stem cells. However, aberrant Wnt signaling leads to intestinal cancer. We investigated the roles of the Wnt pathway in homeostasis of the intestinal epithelium and during malignant transformation in human cells and mice. METHODS: We performed chromatin immunoprecipitation (ChIP) with DNA microarray analysis (ChIP-on-chip) to identify genes regulated by Wnt signaling in human colorectal cancer cells Colo320, DLD1, LS174T, and SW480. Formation of intestinal tumor was induced in C57BL/6J mice using azoxymethane and dextran sulfate. Intestinal tissues from these mice, as well as Apc(+/Min) and Apc(CKO/CKO)/Lgr5-EGFP-IRES-CreERT2 mice, were analyzed by immunohistochemistry and in situ hybridization. RESULTS: We identified promoter regions of 960 genes that interacted with the Wnt pathway nuclear effector T-cell factor 4 in 4 different human colorectal cancer-derived cell lines; 18 of these promoters were present in all chromatin precipitates. Wnt signaling up-regulated a member of the tumor necrosis factor receptor superfamily called TROY. Levels of TROY messenger RNA were increased in human cells with deficiencies in the adenomatous polyposis coli (APC) gene and in cells stimulated with the Wnt3a ligand. Expression of Troy was significantly up-regulated in neoplastic tissues from mice during intestinal tumorigenesis. Lineage tracing experiments revealed that Troy is produced specifically by fast-cycling intestinal stem cells. TROY associated with a unique marker of these cells, leucine-rich repeat-containing G-protein coupled receptor (LGR) 5. In organoids established from the intestinal crypts, Troy suppressed signaling mediated by R-spondin, a Wnt agonist. CONCLUSIONS: TROY is up-regulated in human colorectal cancer cell lines and in intestinal tumors in mice. It functions as a negative modulator of the Wnt pathway in LGR5-positive stem cells.
Keywords: regulace genové exprese u nádorů; Animals; Intestinal Mucosa; Oligonucleotide Array Sequence Analysis; proliferace buněk; apoptóza; kolorektální nádory; Cell Line, Tumor; hybridizace in situ; Apoptosis; Gene Expression Regulation, Neoplastic; Colorectal Neoplasms; RNA nádorová; receptory spřažené s G-proteiny; nádorové buněčné linie; Immunohistochemistry; lidé; Mice; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; polymerázová řetězová reakce s reverzní transkripcí; experimentální nádory; myši; imunohistochemie; Wnt Signaling Pathway; Cell Transformation, Neoplastic; Receptors, Tumor Necrosis Factor; Male; Reverse Transcriptase Polymerase Chain Reaction; Neoplastic Stem Cells; signální dráha Wnt; In Situ Hybridization; Cell Proliferation; Receptors, G-Protein-Coupled; nádorová transformace buněk; RNA, Neoplasm; receptory TNF; zvířata; mužské pohlaví; Mice, Inbred C57BL; Neoplasms, Experimental; nádorové kmenové buňky; střevní sliznice; myši inbrední C57BL; Humans